Epigenetics and Inflammation in Diabetic Nephropathy - Shao, Bao-Yi; Zhang, Shao-Fei; Li, Hai-Di; Meng, Xiao-Ming; Chen, Hai-Yong (Frontiers in Physiology, 2021)
Diabetic nephropathy (DN) leads to high morbidity and disability. Inflammation plays a critical role in the pathogenesis of DN, which involves renal cells and immune cells, the microenvironment, as well as extrinsic factors, such as hyperglycemia, chemokines, cytokines, and growth factors. Epigenetic modifications usually regulate gene expression via DNA methylation, histone modification, and noncoding RNAs without altering the DNA sequence. During the past years, numerous studies have been published to reveal the mechanisms of epigenetic modifications that regulate inflammation in DN. This review aimed to summarize the latest evidence on the interplay of epigenetics and inflammation in DN, and highlight the potential targets for treatment and diagnosis of DN.